AGRICULTURAL GROUNDWATER USE AND RURAL LIVELIHOODS IN SUB-SAHARAN AFRICA: A FIRST-CUT ASSESSMENT - Giordano M. (My University, 2006)
The rapid expansion in agricultural groundwater use in the last few decades has transformed rural economies in large parts of the developing world, in particular South Asia and North China. There has been no such “Groundwater Revolution” in most of sub-Saharan Africa and little is known about the actual role of groundwater use in supporting agricultural livelihoods in the region or opportunities to expand this role in the future. Published literature has been reviewed to paint a preliminary, region-wide picture of the contribution groundwater makes to agriculture, and in turn to rural livelihoods, within sub-Saharan Africa. The findings indicate that groundwater is used on only 1–2 million hectares of cropped area, directly contributing to the livelihoods of 1.5–3% of the rural population. Groundwater also plays a critical role in the vital livestock sector as well as an important indirect role in the supply of domestic water to agricultural households. While data are lacking, these latter two roles likely surpass the direct importance of groundwater to crop production. This suggests that an understanding of the value of agricultural groundwater use in support of rural livelihoods in sub-Saharan Africa should be based on different models than have typically been applied in Asia.
Keywords: AFRICA; AGRICULTURE; GROUNDWATER DEVELOPMENT; LIVESTOCK; SOCIO-ECONOMIC